2016
DOI: 10.1159/000442976
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma PCSK9 Levels Are Associated with Reduced Endotoxin Clearance and the Development of Acute Organ Failures during Sepsis

Abstract: Purpose: We have recently shown that PCSK9 reduces the clearance of endotoxin and is therefore a critical regulator of the innate immune response during infection. However, plasma PCSK9 levels during human sepsis and their relationship to outcomes are not known. Our objective was to determine the relationship between plasma PCSK9 levels and the rate of endotoxin clearance, and then correlate PCSK9 levels with the development of acute organ failures in a cohort of patients with sepsis. Methods: Using human hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
110
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 46 publications
10
110
4
1
Order By: Relevance
“…Similar results have been reported by Boyd et al () who found elevated plasma levels of PCSK9 and increased systemic inflammation during human sepsis. They evaluated the effect of PCSK9 on Escherichia coli endotoxin uptake by the human hepatocyte cells and indicated that hepatic PCSK9 concentrations above physiological plasma levels gradually mitigate bacterial endotoxin clearance of the blood and the development of subsequent organ failure.…”
Section: Role Of Pcsk9 In Sepsis and Septic Shocksupporting
confidence: 91%
“…Similar results have been reported by Boyd et al () who found elevated plasma levels of PCSK9 and increased systemic inflammation during human sepsis. They evaluated the effect of PCSK9 on Escherichia coli endotoxin uptake by the human hepatocyte cells and indicated that hepatic PCSK9 concentrations above physiological plasma levels gradually mitigate bacterial endotoxin clearance of the blood and the development of subsequent organ failure.…”
Section: Role Of Pcsk9 In Sepsis and Septic Shocksupporting
confidence: 91%
“…PCSK9 inhibitors are currently under investigation as lipid-lowering agents because they promote LDL clearance and thus reduce LDL levels, but they may also have an application in clearance of lipid-based pathogens in sepsis. PCSK9 inhibition results in decreased inflammatory cytokine production and physiological responses to endotoxin in septic mice and increased PCSK9 levels are associated with reduced endotoxin clearance and organ failure in sepsis [45, 46]. Although this is a new area of research, it demonstrates that modulation of cholesterol metabolism may have potential as a future application of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PCSK9 knockout and PCSK9 inhibition decrease mortality and markers of inflammation such as plasma cytokines. Furthermore, plasma PCSK9 levels are increased in sepsis and correlated with the development of subsequent cardiovascular and respiratory failure [103] . Additionally, anti-PCSK9 therapy is associated with increased pathogen clearance and decreased inflammatory responses in a murine model of sepsis [104] .…”
Section: Novel Targets For Sepsismentioning
confidence: 99%